A Case Study on Perception of Stakeholders About Computer Training Institutes in West Bengal - Sen, Subhasis (Prabandhan: Indian Journal of Management, 2016)
In spite of being a leading IT destination in the world, India faces disparity in grooming competent computer professionals. The purpose of this study is to bridge the gap between courses taught inÂ computer training institutes in West Bengal (India) and the industry expectations while analyzing issues relevant to IT faculty and students. The primary data was collected using simple random sampling. Statistical measures used are chi-square test for understanding the association of factors relevant to IT faculty and students. Prospective courses for the institutes were ranked using Thurstone Case V analysis. Managerial implications deal with issues related to course fee structure, duration of the course, suitable prospects to target for computer education, and state of remuneration for the faculty members employed in the institutes. The case study has highlighted programs essential for IT aspirants, course fee structure and duration to be considered while designing the course curriculum, significance of student qualification and age, and faculty skills and remuneration which would facilitate the computer training business.